2022
DOI: 10.2500/aap.2022.43.220018
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID: A proposed hypothesis-driven model of viral persistence for the pathophysiology of the syndrome

Abstract: Background: Long COVID (coronavirus disease 2019) syndrome includes a group of patients who, after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), exhibit lingering mild-to-moderate symptoms and develop medical complications that can have lasting health problems. In this report, we propose a model for the pathophysiology of the long COVID presentation based on increased proinflammatory cytokine production that results from the persistence of the SARS-CoV-2 virus or one of its mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 54 publications
0
56
0
3
Order By: Relevance
“…The mechanisms underlying post COVID condition are not clearly defined; however, several pathogenesis models have been put forward. One of the most supported hypotheses is based on the persistence of the virus or a virus component [ 46 ]. Several studies have demonstrated a prolonged SARS-CoV-2 shedding in the respiratory tract, faeces, and intestinal biopsies, even in asymptomatic patients [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying post COVID condition are not clearly defined; however, several pathogenesis models have been put forward. One of the most supported hypotheses is based on the persistence of the virus or a virus component [ 46 ]. Several studies have demonstrated a prolonged SARS-CoV-2 shedding in the respiratory tract, faeces, and intestinal biopsies, even in asymptomatic patients [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to an exacerbated immune response resulting in increased levels of proinflammatory cytokines, including interleukin (IL)-6, IL-1β, and TNF [ 49 , 50 ]. A persistent proinflammatory state could explain organ damage and prolonged symptoms, such as fatigue, headache, and smell impairment [ 46 , 48 ]. Moreover, several types of autoantibodies are produced during SARS-CoV-2 infection due to a molecular mimicry mechanism between self-antigens and spike epitopes [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long COVID, also known as Post COVID-19 condition, defined as the persistence of symptoms 12 weeks after the first acute SARS-CoV-2 infection, affects millions of individuals worldwide [60] and over 50 different symptoms have been associated with this condition [61] . The ultimate cause of this pathology remains an open issue, and different ideas have been posited as its main contributors, including the formation and deposition of blood clots, alterations in the immune system, the persistence of replicating virus in various tissues including the intestinal epithelium, or a combination of all of them [62] , [63] , [64] , [65] . A related, but slightly different scenario, is represented by immunocompromised patients, in which the virus continues its replication for months [66] , [67] .…”
Section: Discussionmentioning
confidence: 99%
“…We agree with the conclusions of Schett et al 1 that targeting of individual cytokines underlying the immunopathogenesis of these conditions may provide a powerful new tool in the treatment of these immunologically-mediated disorders using precision medicine. Further study may elucidate how pathogen or antigen persistence could contribute to these classi cations 12,13 .…”
Section: Discussionmentioning
confidence: 99%